2017
DOI: 10.1007/s12231-017-9373-3
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Use of Malagasy Plants Is Poorly Correlated with Performance in Antimalarial Bioassays

Abstract: Bioassay screening of plant extracts can identify unique lead compounds for drug development, but the “hit rate” from random screening is very low. Targeted screening of medicinal plants has been repeatedly reported to increase the percentage of samples displaying bioactivity. Contrarily, Maranz (2012) suggested that African antimalarial plants were unsuitable sources of antimalarial drugs because high prevalence of malaria would result in rapid evolution of resistance to active compounds that directly targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, a few studies show that plant activity could also increase from in vitro to in vivo. For example, Ngbolua et al [211] showed that the activity of Vernonia ambigua increased from in vitro to in vivo analysis. Other examples include studies by Muthaura et al [20] using Boscia angustifolia, Kweyamba et al [162] using Commiphora Africana, and Ajaiyeoba et al [204] using Annona senegalensis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few studies show that plant activity could also increase from in vitro to in vivo. For example, Ngbolua et al [211] showed that the activity of Vernonia ambigua increased from in vitro to in vivo analysis. Other examples include studies by Muthaura et al [20] using Boscia angustifolia, Kweyamba et al [162] using Commiphora Africana, and Ajaiyeoba et al [204] using Annona senegalensis.…”
Section: Discussionmentioning
confidence: 99%
“…There was also variation between the different assay types. For example, the activities of Vernonia ambigua [211] and Annona senegalensis [204] have been reported to increase from inactive in vitro to very good in vivo. However, a few plant species including Alchornea cordifolia, and Zanthoxylum chalybeum, were observed to be consistently very good between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, assessing to what degree linguistically unique medicinal services are truly effective in the Western sense is beyond the scope of this paper. In many instances, these plants have been proven medicinally effective (12,(22)(23)(24)(25)(26)(27), albeit there are also exceptions (28,29). Regardless of that, here, we treat this knowledge as what it is: part of the cultural heritage of indigenous people.…”
Section: Significancementioning
confidence: 98%
“…Databases of plants used in traditional medicine are widely screened for medically useful compounds (Anand et al, 2019; Pushpangadan et al, 2018; Wink, 2015; Yeung et al, 2020). Although the “jungle medicine” narrative has its share of hype, Western romanticism, and exploitation (Voeks, 2018), and some systematic assays of ethnomedicines have been disappointing (e.g., Applequist et al, 2017), there have been about 60,000 publications on ethnopharmacology, with research increasing dramatically on inflammation, infection, pain, toxicity, cancer and diabetes (Yeung et al, 2020).…”
Section: The Behavioral Immune System Includes Constitutive and Induc...mentioning
confidence: 99%